HISTOPATHOLOGICAL PROFILE OF GASTROINTESTINAL NEUROENDOCRINE TUMORS IN A TERTIARY CARE HOSPITAL - Abbas, F.; Beigh, A.; Khuroo, M.; Farooq, S.; Khuroo, N.; Tazeen, S. (International Journal of Medicine and Medical Research, 2022)
Background. Recently there has been a lot of discussion about the terminology and classification of neuroendocrine tumours of the gastrointestinal tract. The WHO has recommended a change of terminology and classification of these tumours. In 2019 a significant update was done in the WHO classification of neuroendocrine tumours of GIT in which neuroendocrine carcinomas (NECs) are all considered high-grade tumours. Previously, grade 1 and 2 tumours were regarded as neuroendocrine tumours (NETs) and grade 3 neoplasms as NECs. The new classification avoids confusion between these two clinically and molecularly distinct notions. Objective. The aim of the research was to study GI neuroendocrine neoplasms and classify them as per location and Histopathological classification of GI neuroendocrine neoplasms according to the recent WHO classification. To use IHC whenever and wherever required for categorization of GI NET’s. Methods. Over a period of 15 years, a total of 85 cases of neuroendocrine neoplasms of GIT were studied. The histopathological material of patients was reviewed and histopathological diagnosis confirmed. Paraffin embedded tissue blocks were used to study and review the material. Sections from tissue blocks were stained. Five-micron sections were cut and stained. The sections were stained using DAKO LSAB-2® system HRP glass slides coated with 0.5% poly-lysine. Results. Out of 85 cases 40 involved male and 45 female patients. The mean age was 46.4 years; age range 9-85 years. In our study, appendix 24 (28.23%) and stomach 11 (12.95%) were the commonest sites of primary involvement followed by colon (10), ileum (10), duodenum (5), GE junction (5), jejunum (3), oesophagus (2), rectum (2) and gall bladder (1). Metastasis to the liver were observed in 12 patients with known and unknown primary diagnosis. Based on the latest WHO classification 5 patients were classified under NECs and the rest under NETs. Conclusions. Neuroendocrine tumours (NETs) are uncommon malignancies of GIT. Appendix followed by stomach was the most common anatomical site. NET Grade 1 was the most common histological type. IHC markers NSE, Synaptophysin and Chromogranin can be used in diagnosis of NETs.